AVALIAÇÃO POR ESPECTROSCOPIA DE IMPEDÂNCIA ELETROQUÍMICA DO EFEITO CORROSIVO DE BIODIESEL PURO E MISTURAS EM ALUMÍNIO - Cordeiro, Cristiane Italiano (2013)
The use of biodiesel as fuel has presented a great potential in the world, both for its contribution to the environment as well as for being a fuel derived from renewable sources. However, this fuel is causing serious problems of corrosion metallic in materials used in diesel engines, transport systems and storage. In this sense, the present work aims, evaluating the corrosive effect of biodiesel and mixtures in aluminum by means of electrochemical techniques, as the open circuit potential and impedance electrochemical spectroscopy. For such, were used aluminum blades immersed in samples of B100 biodiesel and mixtures of B5 and B4, was also used microemulsion samples for obtaining better answers in the electrochemical trials. The surface of the metalic material was evaluated, after immersion trials, by visualization the optical microscope, in order to identify the effect caused by corrosion. The results obtained for trials showed that aluminum presented a good corrosion resistance in contact with the fuel samples, as well as in samples microemulsion.